Photodynamic therapy - hypericin tetraether liposome conjugates and their antitumor and antiangiogenic activity - Nikola Plenagl; Lili Duse; Benjamin Sebastian Seitz; Nathalie Goergen; Shashank Reddy Pinnapireddy; Jarmila Jedelska; Jana Brüßler; Udo Bakowsky (Taylor & Francis Group, 2019)
Photodynamic therapy (PDT) is an established noninvasive tumor treatment. The hydrophobic natural occurring pigment hypericin shows a lot of attractive properties for the application in PDT. Hence, the administration to biological systems or patients requires the formulation in drug carriers enabling sufficient bioavailability. Therefore, free hypericin was encapsulated by the thin film hydration method or a hypericin-hydroxypropyl-β-cyclodextrin inclusion complex (Hyp-HPβCD) was incorporated by dehydration-rehydration vesicle method in either conventional or ultra-stable tetraether lipid (TEL) liposomes. The hydrodynamic diameter of the prepared nanoformulations ranged between 127 and 212 nm. These results were confirmed by atomic force microscopy. All liposomes showed a good stability under physiological conditions. TEL liposomes which tend to build more rigid bilayers, generate higher encapsulation efficiencies than their conventional counterparts. Furthermore, the suitability for intravenous application was confirmed by hemocompatibility studies resulting in a hemolytic potential less than 20% and a coagulation time less than 50 sec. The uptake of liposomal hypericin into human ovarian carcinoma cells (SK-OV-3) was confirmed using confocal microscopy and further characterized by pathway studies. It was demonstrated that the lipid composition and intraliposomal hypericin localization influenced the anti-vascular effect in the chorioallantoic membrane (CAM). While hypericin TEL liposomes exhibit substantial destruction of the microvasculature drug-in-cyclodextrin TEL liposomes showed no effect. Nevertheless, both formulations yielded severe photocytotoxicity in SK-OV-3 cells in a therapeutic dosage range. Conclusively, hypericin TEL liposomes would be perfectly suited for anti-vascular targeting while Hyp-HPβCD TEL liposomes could deliver the photosensitizer to the tumor site in a more protected manner.